Andrew Jessup - Hilton, Nette, 1946-; Wilcox, Cathy, 1963- (Montville, Qld. : Walter McVitty Books, 1992)
A little girl really misses her friend Andrew Jessup after he moves away, until a new girl moves into Andrew's old house.
For children.
Keywords: Friendship -- Juvenile fiction; Play -- Juvenile fiction; Hobbies -- Juvenile fiction